A framework for managing innovation in higher education: lessons learnt from the UAE iPad initiative. Issue 1 (10th March 2021) - Wilson, Kenesha; Sy, Jobila
Abstract : Purpose: Managing educational innovation in higher education institutions is a complex process that requires specific strategies based on research and proven frameworks. The aim of this paper was to examine how Bolman and Deal's (2003) theoretical framework can be used to analyse organisational change processes and to evaluate the progress and outcomes of an educational innovation initiative at a university in the Gulf. This educational innovation involved the use of iPads in curricular practices to enhance pedagogical strategies and student learning outcomes. Design/methodology/approach: An ethnographic case study methodology was used to make an empirical inquiry that investigated data obtained from direct observations, informal interviews, holistic field notes and documents to better understand a contemporary phenomenon within its real-life context. Findings: A critical analysis of this iPad initiative suggested that the main areas of leading and managing this innovation, through Bolman and Deal's framework, were effectively centred around the human resources, structural and political frames but were less affected by the symbolic frame. Originality/value: The authors provide suggestions, based on their experiences as faculty members and academic administrators, on how such innovations can be effectively led and managed. In addition, a new cross-cultural model is proposed for managing future educational innovations in higher education, particularly in the Gulf region. This new model could also be used to effectively evaluate the implementation and management of other educational changes such as those precipitated by the COVID-19 pandemic.